Effect of overweight and obesity on spirometric parameters in children and adolescent with asthma - Regina N. Khramova; Tatyana I. Eliseeva; Elena V. Tush; D.Yu. Ovsyannikov; Vilya A. Bulgakova; Georgii S. Ignatov; Lamara A. Oganyan; Olga V. Khaletskaya (Exploration of Medicine, 2023)
Aim: Being overweight and obesity are factors in the negative modification of bronchial asthma (BA). The mechanisms of the aggravating effect of obesity on the course of BA have not yet been fully determined, but include changes in external respiration. The aim of the study was to study the effect of being overweight/obesity on spirometric parameters and on the occurrence of dysanapsis in children and adolescents with BA. Methods: It was a cross-sectional, open, single-center study. The data were obtained from 428 patients with atopic BA aged 7 years to 17 years, 12.0 [9.0; 14.0], and 72.9% (312/428) of them were boys. The children were divided into 3 groups: group 1—normal body weight; group 2—overweight; and group 3—obesity. All participants underwent spirometry, the ratio of forced expiratory volume in 1 second (FEV1)/forced vital capacity (FVC) was calculated and the diagnosis of dysanapsis was performed. Results: As body weight increases, a progressive decrease in FEV1/FVC is revealed—group 1: 79.55% [71.37; 85.43]; group 2: 76.82% [70.12; 82.03]; and group 3: 76.28% [67.04; 79.89] P = 0.004; as well as a decrease in Z FEV1/FVC: group 1—1.23 [–2.18; –0.28]; group 2—1.54 [–2.19; –0.68]; and group 3—1.75 [–2.63; –0.90] P = 0.02. Dysanapsis was detected in 37.7% (159/428) of patients. The incidence of dysanapsis increased statistically significantly with increasing body mass index (BMI) and amounted to: with normal body weight—31.7% (77/243), with overweight—42.0% (55/131), and with obesity—50% (27/54) P = 0.016. Conclusions: In children and adolescents with BA, as BMI increases, there is a statistically significant decrease in the ratio of FEV1/FVC, and, consequently, bronchial patency; the incidence of dysanapsis also increases statistically significantly. Taken together, this indicates the formation of an obstructive pattern of external respiration under the influence of being overweight and obesity in children and adolescents with BA.